The Golf Course Mystery. - Steele, Chester K. (Floating Press, 1919)
Can't decide whether you should hit the links or curl up with a can't-put-it-down book? Kill two birds with one stone and read The Golf Course Mystery, a tightly plotted whodunit from the golden era of the genre that is sure to satisfy golf lovers, mystery buffs, and everyone in between.